Late Blight Resistance Evaluation and Genome-Wide Assessment of Genetic Diversity in Wild and Cultivated Potato Species - Duan, Yanfeng; Duan, Shaoguang; Xu, Jianfei; Zheng, Jiayi; Hu, Jun; Li, Xiaochuan; Li, Baoju; Li, Guangcun; Jin, Liping (Frontiers in Plant Science, 2021)
Late blight, caused by the oomycete Phytophthora infestans, is the most devastating disease in potato-producing regions of the world. Cultivation of resistant varieties is the most effective and environmentally friendly way to control potato late blight disease, and identification of germplasms with late blight resistance and clarification their genetic relationship would promote the development of the resistant varieties. In this study, a diverse population of 189 genotypes with potential late blight resistance, consisting of 20 wild species and cultivated S. tuberosum Andigenum group and Chilotanum group, was screened for the presence of late blight resistance by performing challenge inoculation with four P. infestans isolates including one 13_A2 isolate, CN152. Ten elite resources with broad-spectrum resistance and 127 with isolate-specific resistance against P. infestans were identified. To improve the available gene pool for future potato breeding programs, the population was genotyped using 30 SSR markers covering the entire potato genome. A total of 173 alleles were detected with an average of 5.77 alleles per locus. Structure analysis discriminated the 189 potato genotypes into five populations based on taxonomic classification and genetic origin with some deviations. There was no obvious clustering by country of origin, ploidy level, EBN (endosperm balance number) value, or nuclear clade. Analysis of molecular variance (AMOVA) showed 10.08% genetic variation existed among populations. The genetic differentiation (Fst) ranged from 0.0937 to 0.1764, and the nucleotide diversity (π) was 0.2269 across populations with the range of 0.1942 to 0.2489. Further genotyping of 20 K SNP array confirmed the classification of SSRs and could uncover the genetic relationships of Solanum germplasms. Our results indicate that there exits abundant genetic variation in wild and cultivated potato germplasms, while the cultivated S. tuberosum Chilotanum group have lower genetic diversity. The phenotypic and genetic information obtained in this study provide a useful guide for hybrid combination and resistance introgression from wild gene pool into cultivated species for cultivar improvement, as well as for germplasm conservation efforts and resistance gene mining.